Pengaruh Beban Kerja, Ketersediaan APD, Komorbid, Resiliensi dan Stigma Masyarakat Terhadap Tingkat Kecemasan Tenaga Kesehatan di Masa Pandemi Covid-19 - Jubaedah; Sobar (MPI Press, 2022)
Introduction: DKI Jakarta Province still ranks first for the highest number of Covid-19 cases, namely 73,736 cases (25.7%). RSUD X Jakarta is one of the Covid-19 referral hospitals. With the continued high number of Covid-19 cases, health workers on the front line are vulnerable to experiencing conditions of stress and anxiety. Objectives: This research aims to determine the influence of workload, comorbidities, availability of PPE, resilience, and community stigma on the anxiety level of health workers during the Covid-19 pandemic. Methods: This is quantitative research using analytical descriptive methods with a cross-sectional approach. The sampling process was carried out using proportional random sampling based on inclusion and exclusion criteria with 140 samples. The questionnaire uses a Semantic differential scale. Anxiety was measured using the Indonesian version of the GAD-7 (Generalized Anxiety Disorder-7) questionnaire. Research design using SEM (Structural Equation Modeling) via PLS (Partial Least Square). Results: The anxiety level of health workers is influenced by public stigma by 14.74%, workload by 0.58%, availability of PPE by 2.86%, comorbidities by 0.78%, and resilience by 0.11%. The model was able to explain 65.6% of data variability, while 34.4% was explained by other variables not studied in this study. Conclusion: There are direct and indirect influences as well as the magnitude of workload, comorbidities, availability of PPE, resilience, and community stigma on the level of anxiety of health workers during the Covid-19 pandemic at the X Jakarta Regional General Hospital in 2021.